Primordial germ cells (spermatogonial stem cells) of bullfrogs express sex hormone-binding globulin and steroid receptors during seasonal spermatogenesis - Caneguim, Breno Henrique; Beltrame, Flávia Luciana; Da Luz, Juliana Silva [UNESP]; Valentini, Sandro Roberto [UNESP]; Cerri, Paulo Sérgio [UNESP]; Cerri, Estela Sasso [UNESP] (Karger Publishers, 2013)
In vertebrate species, testosterone seems to inhibit spermatogonial differentiation and proliferation. However, this androgen can also be converted, via aromatase, into estrogen which stimulates spermatogonial differentiation and mitotic activity. During seasonal spermatogenesis of adult bullfrogs Lithobates catesbeianus, primordial germ cells (PGCs) show enhanced testosterone cytoplasm immunoexpression in winter; however, in summer, weak or no testosterone immunolabelling was observed. The aim of this study was to confirm if PGCs express stem cell markers-alkaline phosphatase (AP) activity and GFRα1 (glial-cell-line-derived neurotrophic factor)-and verify whether testosterone is maintained in these cells by androgen receptors (ARs) and/or sex hormone-binding globulin (SHBG) in winter. Furthermore, regarding the possibility that testosterone is converted into estrogen by PGCs in summer, the immunoexpression of estrogen receptor (ER)β was investigated. Bullfrog testes were collected in winter and in summer and were embedded in glycol methacrylate for morphological analyses or in paraffin for the histochemical detection of AP activity. GFRα1, AR, SHBG and ERβ expression were detected by Western blot and immunohistochemical analyses. The expression of AP activity and GFRα1 in the PGCs suggest that these cells are spermatogonial stem cells. In winter, the cytoplasmic immunoexpression of ARs and SHBG in the PGCs indicates that testosterone is maintained by these proteins in these cells. The cytoplasmic immunoexpression of ERβ, in summer, also points to an ER-mediated action of estrogen in PGCs. The results indicate a participation of testosterone and estrogen in the control of the primordial spermatogonia during the seasonal spermatogenesis of L. catesbeianus. © 2012 S. Karger AG, Basel.
Keywords: Adult bullfrogs; Androgen and estrogen receptors; Primordial germ cells; Seasonal spermatogenesis; Stem spermatogonia; 2 hydroxyethyl methacrylate; alkaline phosphatase; androgen receptor; estrogen; estrogen receptor beta; glial cell line derived neurotrophic factor; paraffin; sex hormone binding globulin; testosterone; animal cell; bullfrog; cytoplasm; enzyme activity; histochemistry; immunohistochemistry; male; nonhuman; primordial germ cell; priority journal; spermatogenesis; summer; testis; Western blotting; winter; Animals; Cell Differentiation; Estrogen Receptor beta; Humans; Immunohistochemistry; Male; Rana catesbeiana; Receptors, Androgen; Sex Hormone-Binding Globulin; Spermatogenesis; Spermatogonia; Stem Cells; Lithobates; Vertebrata